PENINGKATAN AKTIVITAS FAGOSITOSIS MAKROFAG MENCIT BALB/C DENGAN IMUNOSUPRESI DAN DIINFEKSI C.ALBICANS AKIBAT PEMBERIAN MINYAK BIJI MIMBA: INCREASING MACROPHAGE PHAGOCYTOSIS ACTIVITY IN BALB/C MICE THAT IMMUNOSUPRESSED AND INFECTED WITH C.ALBICANS CAUSED BY OLEUM AZADIRACHTY - Iin Eliana Triwahyuni (Dentika: Dental Journal, 2010)
Majority of fungal infection in mouth is caused by C.albicans. This case increases parallel with increasing the number ofimmunosupressed patient. Mimba (Azadirachta indica) is herbal medicine that has been used as antifungal drug. Besidethat, mimba has immunostimulatory effect. Macrophage phagocytosis, it’s one of natural immunities that plays animportant role in the first immune response againts C.albican infection.The purpose of this research was to know theeffect of oleum azadirachty in macrophage phagocytosis activity of BALB/c mice that immunosupressed and infected byC.albicans. This laboratory experimental research used BALB/c mice that immunosupressed and infected by C.albicans,divided into three groups: group 1 (negative control), group 2 (positive control, were immunosupressed and infected withC.albicans), group 3 (was immunosupressed, infected with C.albicans, and given 75 μl oleum azadirachty). Mice wereimmunosupressed given by 2-3mg/mice subcutan injection of prednisolon one day before infected. Group 2 and group 3were given tetracycline hydrochloride in drinking water (0,83mg/ml) since one day before infected. C.albicansinoculation was given at zero day. On the 2nd day post infection, mice were acclimated and the macrophage phagocytosisactivity was evaluated by latex beat. Data was analysed by One Way Anova test and LSD (p=0.05). The result showedthat there was significant difference between group 2 and group 3. In conclusion, oleum azadirachty could increasemacrophage phagocytosis activity.